Human rather than mouse mesenchymal stem cells in 3D co-culture models boost proliferative and migratory characteristics of colorectal cancer cells through paracrine signalling pathways, highlighting species disconnects - Lu, M. (2022)
Colorectal cancer (CRC) is one of the most prevalent cancers in the world, especially in western countries. It is a multifactorial malignant disease that involves multiple genetic mutations and epigenetic alterations. A large number of patients present with metastasis at the first diagnosis and the five-year survival rate is not ideal. Only a small percentage of the therapeutic agents have been proven to be efficacious for patients after phase III clinical trials. The reason for the disconnection between the preclinical testing and clinical application is in part due to the limitations of experimental models.